Has GVC participation exacerbated inequality of the embodied carbon in fossil energy industry export trade? - Zheng, Minggui; Ni, Jingsheng; Wen, Donghong (Frontiers in Environmental Science, 2024)
This research is based on the WIOD(World Input-Output Database ) database. Firstly, by using multiregional input-output (MRIO), this paper measures fossil energy trade embodied carbon(FEE)hidden carbon data of 39 countries from 2000 to 2014; Secondly, using structural decomposition analysis (SDA), we find what factors affects implicit carbonFEE; Finally, we analyze the impact of GVC on the embodied carbon intensity of fossil energy tradeFEE. This study obtained the following conclusions:(1) Different GVCs have different effects on the embodied carbon in trade. Simple forward, complex forward, and simple back to embedded Play a positive role. The complex back GVC having a negative impact; (2) High -income countries can get greater positive environmental effects through GVC, and middle -income countries can't obtain or obtain less environmental effects; (3) The back GVC affecting the FEE by affecting the proportion of fossil energy consumption. The results show that the FEE shall be jointly responsible for the world's countries, and different countries should make different contributions to the world's environmental protection comprehensively considering factors such as the economic development level of various countries and on. And this proposes relevant policy suggestions in China. Control Yes YesNo Yes YesNo Year FE No No No No Country FE No No No No *** p < 0.01, ** p < 0.05, * p < 0.1 . Control Yes Yes Yes Yes Yes Yes Year FE No No No No No No Country FE No No No No No No *** p < 0.01, ** p < 0.05, * p < 0.1 . Yes Yes Yes Yes Year FE No No No No No No No No Country FE No No No No No No No No *** p < 0.01, ** p < 0.05, * p < 0.1 .